Chromosome structure and aberrations - Bhat, Tariq Ahmad; Wani, Aijaz Ahmad (Springer, 2017)
This book is a compilation of various chapters contributed by a group of leading researchers from different countries and covering up to date information based on published reports and personal experience of authors in the field of cytogenetics. Beginning with the introduction of chromosome, the subsequent chapters on organization of genetic material, karyotype evolution, structural and numerical variations in chromosomes, B-chromosomes and chromosomal aberrations provide an in-depth knowledge and easy understanding of the subject matter. A special feature of the book is the inclusion of a series of chapters on various types of chromosomal aberrations and their impact on breeding behaviour and crop improvement. The possible mechanism, their consequences and role in genetic analysis has been emphasized in these chapters. A few chapters have also been dedicated on various techniques routinely used in the laboratory by students and researchers. Each chapter ends with an extensive bibliography so that the students and researchers may find it relevant to consult more literature on the subject than a book of this size can offer. The book is intended to fulfill the needs of undergraduate and post graduate students of botany, zoology and agriculture besides, teachers and researchers engaged in the field of genetics, cytogenetics, and molecular genetics. In general the readers will find each chapter of the book informative and easy to understand.
Keywords: Chromosomes -- Structure.; elektronické knihy; electronic books